SURVIVAL ANALYSIS OF BREAST CANCER PATIENTS IN KANO STATE - Nabegu, Aminu Aliyu; Muhammad, Musa Uba; Abdullahi, Naziru (FUDMA JOURNAL OF SCIENCES, 2023)
Cancer is a deadly malignant disease and is prevalent in Sub Saharan Africa. Specifically, breast cancer is now the most popular cancer and the second leading cause of death in Nigeria among women. This research is aimed at assessing the length of life of patients and prognostic factors associated with survival of breast cancer patients. Research subjects were breast cancer patients who went to Aminu Kano Teaching hospital (AKTH), patient’s follow-up data were obtained from the medical records and pathological variables were obtained from the department of Pathology from 2018- 2022. The survival analysis was performed using Kaplan Meier, log rank and Cox proportional regression model(semi-parametric). The Kaplan Meier results reveals the overall survival to be 0.75(75%). The median survival time is approximately 44 months, that is the probability that half of the patients have died. From the log-rank test, the survival times significantly differ across groups of Tumor stages, Age groups, Lymph node stages and Treatment Types. Results for the Cox proportional hazards model shows that, Treatment type and Tumor stage breast cancer were the risk factor for death in breast cancer patients. It was found that the hazard of death is twice or more for patients with a tumor characterized as tumor stage IV compared to other tumor stages. The hazard of death for patients on Radiotherapy treatment was 1.4 times as patients on Chemotherapy or Hormonal-therapy treatment. The Proportional Hazard assumption was assessed and all the variables meets the assumption.